Floristic and phytosociological composition of the Leguminosae Juss., family, in Cerrado fragments of the East of Maranhão, Brazil (Research, Society and Development, 2020)
The research was carried out in a Cerrado fragment, located in the east of Maranhão State, aiming to analyze the floristic composition and phytosociological aspects of Leguminosae species. For data collection, the fixed plots method was applied in three areas, with 10 sample units of 10m x 10m per area (30 plots), where all individuals of the Leguminosae family were inventoried. Were analyzed 29 genera and 50 species. Papilionoideae and Mimosa L. were the most representative subfamily and genus in number of species, respectively. Regarding habits, shrub type stood out with 19 species. In the vegetation physiognomy, it was observed that the most representative was Gallery Forest with 24 species. Species richness from the richness estimator (Jackknife 1) showed that the estimated specific richness for the collection sites ranged from 3.12 to 4.25, which indicates a higher potential diversity. Regarding the Maximum Diversity In (S) index, a variation of 2.89-3.09 was observed in the municipality of Coelho Neto, with values higher than the other municipalities. For the Shannon Diversity Index, the values ranged from 2.74 to 2.85, demonstrating considerable diversity in the studied areas. Regarding the dominance index (Simpson), values between 0.95-0.97 were obtained, demonstrating low species dominance. Regarding the Pielou index (J '), values were found between 0.95-0.97, which represents a good homogeneity.